Brave Wolf and the Thunderbird - Medicine Crow, Joseph, 1913- (Tales of the people., 1998)
While hunting, Brave Wolf is snatched by a huge Thunderbird and taken to her nest on a high cliff so he can protect her chicks from a monster.